Prefrontal electrical stimulation in non-depressed reduces levels of reported negative affects from daily stressors - Davis, Nick J. (Frontiers in Human Neuroscience, 2017)
Advances in neuroscience and pharmacology have led to improvements in the cognitive performance of people with neurological disease and other forms of cognitive decline. These same methods may also afford cognitive enhancement in people of otherwise normal cognitive abilities. ‘Cosmetic’, or supranormal, cognitive enhancement offers opportunities to enrich our social or financial status, our interactions with others, and the common wealth of our community. It is common to focus on the potential benefits of cognitive enhancement, while being less than clear about the possible drawbacks. Here I examine the harms or side-effects associated with a range of cognitive enhancement interventions. I propose a taxonomy of harms in cognitive enhancement, with harms classified as (neuro)biological, ethical, or societal. Biological harms are those that directly affect the person’s biological functioning, such as when a drug affects a person’s mood or autonomic function. Ethical harms are those that touch on issues such as fairness and cheating, or on erosion of autonomy and coercion. Societal harms are harms that affect whole populations, and which are normally the province of governments, such as the use of enhancement in military contexts. This taxonomy of harms will help to focus the debate around the use and regulation of cognitive enhancement. In particular it will help to clarify the appropriate network of stakeholders who should take an interest in each potential harm, and in minimising the impact of these harms.